OPTIMALISASI TIM PENYULUH PUSKESMAS UNTUK PENCEGAHAN RISIKO ANEMIA PADA IBU HAMIL DENGAN PANGAN LOKAL - Wahyunita, Sari; Rahman, Andri Nur; Ramadhani, Aulia; Sidiq, Abdrurrahman (LPPM Universitas Bina Bangsa, 2024)
The use of local food as a strategy to prevent anemia is not optimal; one of the causes is a lack of public knowledge and awareness about the importance of nutrition in local food. Effective counseling by nutritionists can help change people's behavior in choosing and consuming food. A series of activities are the answer to the problem, namely increasing knowledge through direct counseling and PMT (supplemental feeding) cooking demonstrations using local food, namely the use of the Kelakai plant as a nugget mixture. The community is given an understanding of local food diversity, which can help increase nutritional intake, especially iron. Extension workers encourage people to take advantage of local food that is easy to obtain and affordable, namely the Kelakai plant, which is processed into nuggets. Extension workers also provide training to pregnant women on how to cook and serve local food to keep it nutritious. The activity began by conducting a pre-test through questions about knowledge of anemia in pregnant women. The aim was to see the descriptions of participants, namely pregnant women, regarding knowledge of anemia, symptoms, and consequences of anemia. The taste of Nugget received quite good ratings from respondents, especially for texture and color. The taste also received positive reviews, although some respondents felt the aroma could be improved. The comments provided can be used to improve product quality